REPRODUCTIVE CONDITION ASSOCIATED TO CHANGES IN THE LIPID-SOLUBLE ANTIOXIDANT CAPACITY AND DAMAGE TO LIPIDS IN THE SEA URCHINS LOXECHINUS ALBUS (ECHINODERMATA: ECHINOIDEA) - Pérez, Analía F. (2011)
The hypothesis of this study was that oxidative damage in the lipid phase of the gonad of the sea urchin Loxechinus albus increased during gametogenesis. Six different male and female reproductive conditions (reproductive stages) were described: (a) immature, (b) growing, (c) premature I, (d) premature II, (e) mature, and (f) spawned. The content of the lipid-soluble antioxidants, as well as the damage to lipids (assessed as the content of 2-thiobarbituric acid reactive substances (TBARS) and the content of lipid radicals) were analyzed. The content of the lipid-soluble antioxidants α-tocopherol (α-TH), β-carotene, and echinenone decreased during gametogenesis. In contrast, the content of both TBARS and lipid radicals increased. However, the consumption of lipid-soluble antioxidants was not sufficient to efficiently control lipid damage since the ratio of TBARS content/ α-TH content, taken as an index of damage/protection ratio, significantly increased during the mature stage. Therefore, an active food intake to incorporate antioxidants to the diet is required to adequately prepare the gonad for the next reproductive cycle.